Synthesis and Preliminary Biological Activity Evaluation of New N- Substituted Phthalimide Derivatives - Sahib, Halah A.; H. Mohammed, Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2020)
AA new series of bases of Schiff (H2-H4) derived from phthalic anhydrideweresynthesized. These Schiff bases were prepared by the reaction of different amines (tyrosine methyl ester, phenylalanine methyl ester, and isoniazid) with the phthalimide derived aldehyde with the aid of glacial acetic acid or triethylamine ascatalysts. All the synthesized compounds were characterized by (FT-IR and 1HNMR) analyses and were in vitro evaluated for their antimicrobial activity against six various kinds of microorganisms. All the synthesized compounds had been screened for their antimicrobial activity against two Gram-positive bacteria “Staph. Aureus, and Bacillus subtilis”, two Gram-negative bacteria “Escherichia coli, and Klebsiella pneumoniae”, and two fungi species “Candida tropicalis and Candida albicans” using concentrations of 62.5, 125 and 250 µg\mLof derivative in dimethyl sulfoxide(DMSO). All the synthesized compounds showed no activity at all against Gram-positive bacteria, for Gram-negative bacteria and fungi they showed moderate or no activity except compound H1revealedhigh antifungal activityagainstCandida tropicalisat concentrations 125 and 250 µg\ mL.Keywords: Schiff base, phthalic anhydride, antimicrobial.